Vision Loss and Subretinal Yellow Deposits Following Cytostatic Therapy for Early-Stage Breast Cancer: a Case Report - Dias-Santos, A (2013)
Introduction/Objective: To report a case of ocular toxicity related to two chemotherapeutic regimens approved for early-stage breast cancer: doxorubicin (Adriamycin®) and cyclophosphamide – AC protocol; carboplatin and docetaxel combination. Material and Methods: We report a case of a 39-year-old woman with stage I ductal invasive breast cancer, who presented with bilateral painless reduced visual acuity two days after the first administration of intravenous doxorubicin and cyclophosphamide. Results: The best corrected visual acuity (BCVA) was 20/100 in both eyes and the fundoscopy revealed pearly-yellow lesions in the posterior pole and mid-peripheral retina bilaterally, with retinal pigment epithelium hypertrophy in the right eye (RE). These lesions were hyperfluorescent on fluorescein angiography and appeared as drusen-like deposits under the retinal pigment epithelium in the optical coherence tomography (OCT). The electrophysiological study revealed a diffuse dysfunction of bipolar cells and photoreceptors and macular dysfunction, more pronounced in the RE. Goldmann visual field testing, color vision and optic nerve OCT were normal. 72 hours after the treatment, her BCVA improved spontaneously to 20/25 in the RE and 20/20 in the left eye (LE). A similar drop in BCVA was observed after a second cycle of AC protocol and after second-line cycle of carboplatin and docetaxel, with subsequent recover. The remaining observation remained remarkably similar. Discussion: This can be the first report of a rare idiosyncratic reaction to AC protocol and carboplatin-docetaxel chemotherapeutic regimens, approved for early-stage breast cancer.